EPIDEMIOLOGY AND CLINICAL PROFILE OF DENGUE AND CHIKUNGUNYA INFECTION AND SEROTYPE DIVERSITY OF DENGUE VIRUS IN NORTHERN INDIA - SHAILPREET K SIDHU; MANINDER KAUR; KANWARDEEP SINGH; NEELU NAGPAL; MAASHA BANGARH; RATNEEV KAUR; HARSHIL SIDHU (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: Dengue and chikungunya (CHIKV) are major public health problem and are notable arthropod viral infections due to their expanding geographical distribution. As there are multiple serotypes of dengue virus circulating concurrently with CHIKV virus, the present study was conducted to describe the seroprevalence, epidemiological characteristics, clinical profile, seasonal trends, coinfection, and prevalent circulating dengue virus serotypes (DENVs). Methods: Serum samples from clinically suspected cases of dengue and CHIKV were subjected to serological testing by performing enzyme-linked immunosorbent assay. The particulars of the patient including case history, demographic characteristics, co-morbidities, clinical features, and evolution of symptoms were recorded. Further, samples which were positive for NS1 antigen were subjected to multiplex real-time reverse transcription polymerase chain reaction testing for typing of DENVs 1, 2, 3, and 4. Results: Seroprevalence of dengue and CHIKV was reported to be 23.39% and 20.65%, respectively. Maximum number of cases were reported in the age group of 21–40 years. Common clinical presentations in dengue patients were fever, myalgia, headache, and nausea/vomiting whereas in CHIKV, the most common symptoms were fever, myalgia, and joint pains. On molecular surveillance, DENV-2 was detected in maximum cases (73.33%) followed by serotype 3 (11.66%). Conclusion: Dengue and CHIKV infections continue to co-exist and there is substantial overlap in their clinical presentation. Simultaneous diagnosis of both viruses will help in evaluation, appropriate treatment, and prophylactic measures. Surveillance of DENVs needs to be closely monitored for the emergence of new serotypes.